Compare the Outcomes of Sclerotherapy with Bleomycin Versus 15% Hypertonic Saline in Children with Cystic Hygroma - Gauri Shankar Pandit, Ranjana Kumari Pandit, Rija Nawaz Abbassi, Nahida Burki, Faisal Mahmood, Asad Iqbal, Nadeem Akhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The goal of this research is to evaluate the efficacy of bleomycin sclerotherapy against hypertonic saline (at 15%) in treating cystic hygroma in children. Study Design: Comparative study Place and Duration: Children Hospital, Pakistan Institute of Medical Sciences PIMS Islamabad. July 2021-Feb 2022. Methods: There were 52 children of both genders with cystic hygroma were included in this study. Included children had age 2 months to 12 years. After taking informed written consent from the parents of children detailed demographics age, sex, weight and place of living were recorded. Patients were equally categorized in two groups. 26 patients in group I received sclerotherapy with bleomycin and in group II 26 children received 15% hypertonic saline. Post-treat outcomes among both groups were assessed and compared. SPSS 22.0 was used to analyze all data. Results: Among 52 children, there were 32 (61.5%) males and 20 (38.5%) females. Mean weight of the children was 14.7±5.37 kg and mean age was 6.9±9.54 years. Majority of the cases 34 (65.4%) were from rural areas and 18 (34.6%) were had urban residency. Most common site of lymphangioma was neck and axilla. In group I 18 (69.2%) children received four sessions of bleomycin. We found higher number of effectiveness in patients of group I 25 (96.2%) as compared to group II in 22 (84.6%) cases with p value <0.009. Frequency of wound infection and recurrence rate was also higher in group II. Conclusion: We concluded in this study that the use of sclerotherapy with bleomycin was an effective and useful in the treatment cystic hygroma children in terms of higher number of excellent results as compared to 15% hypertonic saline. Except this recurrence rate and complications were also not seen in sclerotherapy with bleomycin group. Keywords: Bleomycin, Sclerotherapy, Cystic Hygroma, Recurrence, Wound Infection, 15% Hypertonic Saline